Determination of a metabolite of nifursol in foodstuffs of animal origin by liquid–liquid extraction and liquid chromatography with tandem mass spectrometry. Issue 3 (13th January 2017) - Wang, Chuanxian; Qu, Li; Liu, Xia; Zhao, Chaomin; Zhao, Fengjuan; Huang, Fuzhen; Zhu, Zhenou; Han, Chao
Abstract : An analytical method has been developed for the detection of a metabolite of nifursol, 3, 5‐dinitrosalicylic acid hydrazide, in foodstuffs of animal origin (chicken liver, pork liver, lobster, shrimp, eel, sausage, and honey). The method combines liquid chromatography and tandem mass spectrometry with liquid–liquid extraction. Samples were hydrolyzed with hydrochloric acid and derivatized with 2‐nitrobenzaldehyde at 37°C for 16 h. The solutions of derivatives were adjusted to pH 7.0−7.5, and the metabolite was extracted with ethyl acetate. 3, 5‐Dinitrosalicylic acid hydrazide determination was performed in the negative electrospray ionization method. Both isotope‐labeled internal standard and matrix‐matched calibration solutions were used to correct the matrix effects. Limits of quantification were 0.5 μg/kg for all samples. The average recoveries, measured at three concentration levels (0.5, 2.0, and 10 μg/kg) were in the range of 75.8–108.4% with relative standard deviations below 9.8%. The developed method exhibits a high sensitivity and selectivity for the routine determination and confirmation of the presence of a metabolite of nifursol in foodstuffs of animal origin.